ANALYSIS OF TEACHER STRATEGIES IN LEARNING SPEAKING IN MENTENG STATE PRIMARY SCHOOL 01 - Fadhilah, Rifdah; Febriani Sya, Mega; Muhdiyati, Iyon (Fakultas Agama Islam dan Pendidikan Guru, 2025)
When carrying out teaching activities in class, a teacher needs to prepare learning strategies that will be used to achieve learning objectives. The purpose of writing this article is to find out and analyze the strategies used by teachers when teaching speaking. The method used in writing this article is using a literature review from 10 national journals that discuss speaking learning strategies in elementary schools. The results of the review obtained are that teachers who teach using learning strategies will be more optimal in learning activities in the classroom. By using various learning methods, the learning atmosphere will be enjoyable and learning objectives can be achieved.